Effects of Tm3+ Additions on the Crystallization of LaF3 Nanocrystals in Oxyfluoride Glasses: Optical Characterization and Up‐Conversion. Issue 2 (12th December 2012) - de Pablos‐Martín, A.; Ristic, D.; Bhattacharyya, S.; Höche, Th.; Mather, G.C.; O Ramírez, M.; Soria, S.; Ferrari, M.; Righini, G.C.; Bausá, L.E.; Durán, A.; Pascual, M.J.; et al.
<x xml:space="preserve">Abstract</x> The influence of the addition of 1 mol% Tm2O3 on the nanocrystallization of LaF3 in a glass of composition 55SiO2–20Al2O3–15Na2O–10LaF3 (mol%) has been studied. Tm2O3 affects the phase separation in the glass and delays the onset of crystallization with respect to the undoped glass. Additionally, the maximum LaF3 crystal size is slightly greater than that in the undoped glass–ceramics. The microstructural and compositional changes in the glass matrix have been studied using several techniques, including viscosity, dilatometry, X‐ray and neutron diffraction (XRD, ND), quantitative Rietveld refinement, transmission electron microscopy (TEM), differential scanning calorimetry (DSC), and Raman spectroscopy. Photoluminescence measurements indicate that the Tm3+ ions are distributed between the glassy matrix and LaF3 crystals. Eu2O3 has been used as structure probe and part of the Eu3+ ions are reduced to Eu2+ when incorporated in the LaF3 nano‐crystals. Up‐conversion spectra under IR‐excitation show a higher intensity of the blue emission in the Tm‐doped glass–ceramic compared with that in the glass.